Plant Species for the Manufacture of Malagasy Traditional Alcoholic Beverages - Randrianarivony, Tabita N.; Rakotoarivony, Fortunat; Randrianasolo, Armand; Hart, Robbie (Ethnobiology Letters, 2024)
Alcoholic beverages are an important component of many traditional events of Madagascar, including life-course events like male circumcision, burial and exhumation. As with many other parts of Malagasy customary practice, these beverages incorporate the unique and richly diverse flora of Madagascar. We conducted structured interviews with producers and consumers of Malagasy Traditional Alcoholic Beverages (MTABs) in 10 regions of Madagascar, spanning the island from east to west and north to south. We documented 75 plant species used to make three types of Malagasy Traditional Alcoholic Beverages: distilled toaka gasy, fermented cane wine betsa, and fermented palm wine trembo. Of the 75 species, 14 were main materials/main ingredients, 55 were additives during fermentation, and six were used as tools for distillation. The species were diverse, occurring in 35 plant families. Particularly species-rich families were Arecaceae (palm family) as main materials and Rutaceae (citrus family) as additives.